Determinant Factors of the Implementation of the Bureaucratic Simplification Policy in the West Java Provincial Government - Dwi Wahyuni; Eko Prasojo (Greenation Research & Yayasan Global Resarch National, 2025)
Following the lengthy journey of its bureaucracy from independence to the reform era, Indonesia is still working to modernise its system. The bureaucratic simplification policy, which addresses the difficulties of a quickly evolving organisational environment, ushers in a new age for the Indonesian bureaucracy amid the ongoing bureaucratic reform. The bureaucratic simplification agenda has faced particular challenges for municipal governments. The West Java Provincial Government has been judged successful in putting the bureaucratic simplification agenda into practice since it was passed. Thus, the purpose of this study is to examine the variables affecting the West Java Provincial Government's application of the bureaucratic simplification program. Additionally, this study develops methods for improving the West Java Provincial Government's execution of the bureaucratic simplification program. This study employs a qualitative methodology, gathering data via document analysis and interviews. The study's findings show that the West Java Provincial Government's bureaucratic simplification policy's implementation context and content are significantly out of balance. The policy's overall content demonstrates high success in the structural aspect, but there are significant gaps in the dimensions of human resource quality, work culture, and perceived benefits. Although the implementation context demonstrates a high level of leadership commitment and creative initiatives, the efficacy of the policy in the field is hampered by inadequacies in the qualitative commitment aspect of civil servants.